Functional Identification and Characterization of Leucokinin and Its Receptor in the Fall Webworm, Hyphantria cunea - Sun, Lili; Ma, Heting; Gao, Yuan; Wang, Zhiying; Cao, Chuanwang (Frontiers in Physiology, 2021)
Behavior and physiology are orchestrated by neuropeptides acting as central neuromodulators and circulating hormones. Leucokinin (LK) is an intercellular signaling molecule that mediates many physiological and behavioral processes. However, the function of LK associated with the environmental stress and feeding behavior is little known in the fall webworm, Hyphantria cunea. Our overarching objective is to understand the function of LK and LK receptor (LKR) neuroendocrine system in H. cunea. In present study, the results showed LK/LKR is expressed in different developmental stages and various tissues of the fall webworm. Knockdown of HcLK and HcLKR by microinjecting target dsRNA was a set of effects on H. cunea, including feeding promotion, resistance increase to desiccation and starvation stress, and regulation of water steady state. Variations of mRNA transcription levels in insulin-like peptide genes suggested an essential role for this gene in the survival of H. cunea. A candidate receptor-ligand pairing for LK was identified in a larval transcriptome of the fall webworm. In a heterologous expression system, we used calcium assay to demonstrate that LKR is activated by HcLKs in a dose-dependent manner 50% effective concentrations (EC50) value of 8.44–90.44 nM. Herein, these presented results mark the first comprehensive study of a LK and LKR in the fall webworm from gene to behavior.